Heterogeneity and Asset Prices: An Intergenerational Approach - Gârleanu, Nicolae; Panageas, Stavros (Journal of Political Economy, 2023)
In an overlapping-generations economy, the consumption growth of a given cohort member (the “marginal agent”) differs from the aggregate consumption growth. A cohort member is faced with long-run consumption uncertainty even in the absence of aggregate (and within-cohort) consumption risk. This uncertainty allows the model to account for several stylized asset-pricing facts (high market price of risk and volatility, return predictability, low and nonvolatile interest rate) despite deterministic macroeconomic aggregates and inequality measures that are contemporaneously uncorrelated with asset returns. We devise and implement a methodology to measure the marginal agent’s consumption growth and evaluate the model’s quantitative implications.